2001
DOI: 10.1038/oby.2001.81
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Sarcopenia after Menopause Are Reversed by Sex Hormone Replacement Therapy

Abstract: SØRENSEN, MORTEN BECK, ANNE METTE ROSENFALCK, LISELOTTE HØJGAARD, AND BENT OTTESEN. Obesity and sarcopenia after menopause are reversed by sex hormone replacement therapy. Obes Res. 2001;9:622-626. Objective: Menopause is linked to an increase in fat mass and a decrease in lean mass exceeding age-related changes, possibly related to reduced output of ovarian steroids. In this study we examined the effect of combined postmenopausal hormone replacement therapy (HRT) on the total and regional distribution of fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(116 citation statements)
references
References 38 publications
3
112
0
1
Order By: Relevance
“…Post-menopausal estrogen replacement therapy (ERT) was often recommended for prevention and treatment of osteoporosis (Glazier & Bowman 2001) as well as for maintaining muscle strength and mass (Phillips et al 1993, Sorensen et al 2001. However, ERT is associated with potential side effects on reproductive tissues, such as breast cancer and refused as being unnatural by women (Glazier & Bowman 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Post-menopausal estrogen replacement therapy (ERT) was often recommended for prevention and treatment of osteoporosis (Glazier & Bowman 2001) as well as for maintaining muscle strength and mass (Phillips et al 1993, Sorensen et al 2001. However, ERT is associated with potential side effects on reproductive tissues, such as breast cancer and refused as being unnatural by women (Glazier & Bowman 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that estrogen therapy may attenuate the accumulation of central fat in postmenopausal women (17)(18)(19)(20). In the PEPI trial (21), less weight gain or increase in waist and hip circumferences were registered in women who received ECP therapy compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely perceived that HRT causes weight gain [21,22], although data from clinical trials examining weight gain is inconclusive, in some studies showing an increase in overall body weight [15,[23][24][25] and others showing no significant effect [26][27][28][29][30][31][32]. It is possible that differences in measures of weight gain, physical activity of responders, HRT regimens (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the use of micronized progesterone), may account for the differences observed in these trials. Some studies indicate that HRT may have positive effects on body fat distribution [25,[28][29][30][31][32], for example, data from the Post-menopausal Estrogen/Progestin Interventions (PEPI) trial showed that HRT may reduce central adiposity [32], although the current evidence is inconclusive [26].…”
Section: Introductionmentioning
confidence: 99%